Fundamentos estruturais do registro bibliográfico: revisitando a compreensão de Seymour Lubetzky sobre a entrada principal representativa da obra e sua manifestação - Marcelo Nair dos Santos (2019)
This study comes back to Seymour Lubetzky’s studies on cataloging rules through which he explained the function of the main entry. Cataloging should be thought fundamentally as Lubetzky did in the 1950s, when he evaluated a set of rules of his time. His theoretical analysis model is a critical and methodological path to the establishment of cataloging rules. His studies revealed that the bibliographic record must represent a publication as a manifestation of a given work. Therefore, we have hypothesized that Lubetzky's thoughts are still valid in the insufficient foundations of Cataloging by the Anglo-American tradition. Hence it is proposed a study that aims to revisit the ideas of Lubetzky, in order to evaluate the consistency of his understanding for the present day. We have delimited our material object of the research to bibliographic record, especially the access point representing the entity work, which will be examined from the theoretical perspective of Lubetzky. This research is carried out in an exploratory qualitative approach and it uses bibliographic and documentary research as predominant methodological procedures. In this way, the development of the research is divided according to the significant moments of the Cataloging: the prior cataloging context of Lubetzky's studies; the analysis and repercussion of the Lubetzky's studies on cataloging rules, from which he indicated a specific function for the main entry in Cataloging; the way followed by Anglo-American cataloging rules after Lubetzky's studies about the function of the main entry; and studies and models of the Cataloging through which the bibliographic record can be structured, according to the main entry function proposed by Lubetzky. We concluded that the function of the main entry revealed by Lubetzky is still sound for the cataloging of our days, because representing the publication as manifestation of a work in bibliographic record is a fundamental aspect that cannot be ignored in the cataloging practice that observes the relationship of the equivalent and derivative publications of a literary unit.